Analysis and design of marine structures V proceedings of the 5th International Conference on Marine Structures (MARSTRUCT 2015), Southampton, UK, 25-27 March 2015 - Soares, C. Guedes; Shenoi, R. A. (CRC Press, Taylor & Francis Group, 2015)
Analysis and Design of Marine Structures V contains the papers presented at MARSTRUCT 2015, the 5th International Conference on Marine Structures (Southampton, UK, 25-27 March 2015). The MARSTRUCT series of conferences started in Glasgow, UK in 2007, the second event of the series took place in Lisbon, Portugal (2009), while the third was in Hamburg, Germany (2011), and the fourth in Espoo, Finland (2013). This book is essential reading for academics, engineers and all professionals involved in the area of design of marine and offshore structures.